2019
DOI: 10.1038/s41467-019-10725-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer accessibility and CTCF occupancy underlie asymmetric TAD architecture and cell type specific genome topology

Abstract: Cohesin and CTCF are master regulators of genome topology. How these ubiquitous proteins contribute to cell-type specific genome structure is poorly understood. Here, we explore quantitative aspects of topologically associated domains (TAD) between pluripotent embryonic stem cells (ESC) and lineage-committed cells. ESCs exhibit permissive topological configurations which manifest themselves as increased inter- TAD interactions, weaker intra-TAD interactions, and a unique intra-TAD connectivity whereby one bord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 56 publications
7
87
0
Order By: Relevance
“…Whether these epigenetic modifications are important for TADs establishment is not determined at this time. However, it is reasonable to speculate that chromatin states can affect the process of cohesin-mediated extrusion as for super-enhancers 44 . Surprisingly, neither the density of genes nor RNA expression was found enriched at the borders of either cluster of TADs (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Whether these epigenetic modifications are important for TADs establishment is not determined at this time. However, it is reasonable to speculate that chromatin states can affect the process of cohesin-mediated extrusion as for super-enhancers 44 . Surprisingly, neither the density of genes nor RNA expression was found enriched at the borders of either cluster of TADs (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…However, genes sharing these domains may have different regulatory wiring and expression patterns ( Hnisz et al., 2016 ; Schoenfelder and Fraser, 2019 ). In addition, active enhancers might themselves function as TAD boundary elements ( Barrington et al., 2019 ; Bonev et al., 2017 ), and contacts between superenhancers recover more rapidly upon reversal of cohesin depletion compared with other chromosomal loops ( Rao et al., 2017 ). These observations suggest that factors acting in cis to DNA regulatory elements are involved in establishing their chromosomal interactions.…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that much like mitotic chromosome compaction, the formation of major features of interphase chromosomes, such as TADs, "dots," and "stripes" requires avoiding unlooped gaps, either between LEFs or between LEFs and TAD boundaries. One-sided extrusion can form TADs and stripes by enhancing local chromatin contacts , as observed in Hi-C experiments (Dixon et al, 2012;Nora et al, 2012;Sexton et al, 2012;Rao et al, 2014;Fudenberg et al, 2016;Vian et al, 2018;Barrington et al, 2019). However, dots (Rao et al, 2014;Krietenstein et al, 2020) can only be generated by "effectively two-sided" loop extrusion because such extrusion can reliably bring together TAD boundaries (e.g., convergently oriented CTCF binding sites (Rao et al, 2014;Guo et al, 2015;Sanborn et al, 2015;de Wit et al, 2015;Vietri Rudan et al, 2015)).…”
Section: Topologically Associated Domainsmentioning
confidence: 99%